Intellectualism against empiricism - Castellano, Federico (2014)
Intellectualism is the philosophical view that thinking involves the activity of reason-giving. In this paper I argue that the intellectualist point of view is incompatible with any form of empiricism. First, I show that Traditional Empiricism collapses because it brings together two conflicting theses: the intellectualist thesis according to which the normative properties of thoughts depend (rest) upon the activity of reason-giving, and the intuitive empiricist thesis according to which the normative properties of empirical thoughts derive from perceptual experience. Second, I argue that McDowell?s Minimal Empiricism collapses as well because of his attempt to make sense of an over-intellectualized and contradictory variety of empiricism: one that preserves both an intellectualist approach to thought and a conceptual but passive approach to perceptual experience.